A Legal Perspective on the Opportunities and Challenges of the Sharia Notary Profession in Indonesia - Adil, Ustad; Arifin, Tajul (UIN Siber Syekh Nurjati Cirebon, 2025)
The demand for Sharia-based legal services in Indonesia is steadily increasing, highlighting the urgency of establishing the position of Sharia Notary as a bridge between Islamic law and positive law. This study employs a normative juridical approach with qualitative methods. Data were collected through literature review, regulatory analysis, and in-depth interviews with notaries, academics, and practitioners of Sharia law. The main findings indicate that despite significant opportunities for developing the Sharia Notary—particularly in supporting the national Sharia economic system—substantial challenges continue to hinder its implementation. These challenges include the absence of specific regulations, limited educational infrastructure and professional certification, and the lack of harmonious integration between Sharia law and the national legal system. This study presents a novelty in the form of a conceptual framework proposal for the legalization and institutionalization of the Sharia Notary position in Indonesia, through three strategic recommendations: establishing specific regulations, integrating Sharia legal curriculum into notarial education, and strengthening the supervisory role of Sharia oversight bodies. The Sharia Notary plays a strategic role in ensuring legal certainty in Sharia transactions and strengthening trust in a fair, inclusive legal system.Keywords: Sharia Notary; Islamic law; positive law; regulation; Sharia economy.